2006
DOI: 10.1104/pp.106.085886
|View full text |Cite
|
Sign up to set email alerts
|

IMMUTANS Does Not Act as a Stress-Induced Safety Valve in the Protection of the Photosynthetic Apparatus of Arabidopsis during Steady-State Photosynthesis

Abstract: IMMUTANS (IM) encodes a thylakoid membrane protein that has been hypothesized to act as a terminal oxidase that couples the reduction of O 2 to the oxidation of the plastoquinone (PQ) pool of the photosynthetic electron transport chain. Because IM shares sequence similarity to the stress-induced mitochondrial alternative oxidase (AOX), it has been suggested that the protein encoded by IM acts as a safety valve during the generation of excess photosynthetically generated electrons. We combined in vivo chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
101
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 77 publications
10
101
2
Order By: Relevance
“…Taken together, these results do not support the model of IM as a safety valve to regulate the redox state of the PQ pool during stress and acclimation in fully developed Arabidopsis leaves. By contrast, the meta-analysis revealed that IM did appear to be strongly regulated by development in Arabidopsis (Rosso et al, 2006). This is consistent with the observations of Aluru et al (2001Aluru et al ( , 2009 who suggested that IM is required to protect against the potential for photooxidation during the development of chloroplasts, amyloplasts, and etioplasts.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Taken together, these results do not support the model of IM as a safety valve to regulate the redox state of the PQ pool during stress and acclimation in fully developed Arabidopsis leaves. By contrast, the meta-analysis revealed that IM did appear to be strongly regulated by development in Arabidopsis (Rosso et al, 2006). This is consistent with the observations of Aluru et al (2001Aluru et al ( , 2009 who suggested that IM is required to protect against the potential for photooxidation during the development of chloroplasts, amyloplasts, and etioplasts.…”
Section: Introductionsupporting
confidence: 87%
“…If the PQ pool remains reduced due to the lack of IM, carotenoid biosynthesis is blocked at the phytoene desaturase step, phytoene accumulates, and photobleaching results from an increase in chloroplastic ROS (Wetzel et al, 1994;Wu et al, 1999). Consistent with the notion that white sectoring is triggered by photooxidation (Aluru et al, 2009) is the fact that the variegated phenotype can be suppressed in im plants when grown under low-light conditions (Ré dei, 1963;Wetzel et al, 1994;Aluru and Rodermel, 2004;Rosso et al, 2006).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…During de-etiolation, the NDH-like complex rapidly starts to interact with PSI, and after just 48 h in light, the PSI-NDH supercomplex is assembled (Peng et al 2008). This result may support the speculated co-operation between NDH and the plastid terminal oxidase PTOX, which is known to be crucial for the early leaf development and for the proper chloroplast biogenesis (Rosso et al 2006(Rosso et al , 2009. Alternatively, the etioplastic NDH-like complex might be physiologically nonfunctional until the appearance of its assembly partner, PSI.…”
Section: Ndh Complexes In Electron Transfersupporting
confidence: 58%